Contribution in the study of Aujeszky’s disease. II. Isolation and study of Aujeszky’s virus from piglets and rats - ΣΤΟΦΟΡΟΣ Ε.; ΜΑΣΤΡΟΠΑΝΝΗ Μ.; ΑΞΙΩΤΗΣ Ι.; ΧΑΤΖΗΜΑΝΩΛΑΚΗΣ Κ.; ΑΝΑΓΝΩΣΤΟΥ Λ.; ΛΙΟΥΠΗΣ Σ.; ΛΟΥΚΑ Σ.; ΜΠΑΛΤΑΤΖΗ Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
The virus of Aujeszky’s disease isolated from three outbreaks of the disease in piglets and rats was studied. Physicochemical, biological and serological methods were used for virus identification. High mortality with nervous symptoms in suckling piglets and abortions with agalaxia were the main sym tomos. In one outbreak the virus infected also cattle. Dogs and cats of the farm were died.